Machine Learning for Detection of Distributed Denial-of-Service Attacks from Queries Executed in DBMS - Chagas, Danilo A. M.; Rocha Filho, Geraldo P.; Meneguette, Rodolfo I.; Bonacin, Rodrigo; Gonçalves, Vinícius P. (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS); 2023: Anais do XXVIII Workshop de Gerência e Operação de Redes e ServiçosDO - 10.5753/wgrs.2023.766, 2023)
Denial-of-Service (DoS) attacks have been extensively studied in the literature, especially in their most dangerous form, the Distributed Denial-of-Service (DDoS). Database, a critical infrastructure for services, has mechanisms for recording information (logs) of SQL queries and sessions. Although they are vulnerable to DDoS, they are not entirely covered by commercial tools or research on such a detection. Machine Learning (ML) techniques are highly effective in identifying patterns in data such as database SQL logs. Thus, this work proposes the application of ML to detect DDoS attacks on a database from the logs of queries executed on it. As a result, the classification obtained an F1-score of 94.44%, which indicates the effectiveness of the proposed approach.